Child migration in Africa - Hashim, Iman.; Thorsen, Dorte; Nordiska Afrikainstitutet (London ; New York : Zed Books ; Uppsala, Sweden : In association with the Nordic Africa Institute, 2011)
Child Migration in Africa explores the mobility of children without their parents within West Africa. Drawing on the experiences of children from rural Burkina Faso and Ghana, the book provides rich material on the circumstances of children's voluntary migration and their experiences of it. Part of the groundbreaking Africa Now series, Child Migration in Africa is an important and timely contribution to an under-researched area.
"First published in association with the Nordic Africa Institute, Uppsala, Sweden in 2011" -- T.p. verso.
Includes bibliographical references (p. 132-144) and index.
Keywords: Children. Child development Including child rearing, child life, play, socialization, children's rights; Unaccompanied immigrant children -- Africa, West; Children -- Africa, West -- Social conditions